2021
DOI: 10.3390/cancers13194749
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics, Care Trajectories and Mortality Rate of SARS-CoV-2 Infected Cancer Patients: A Multicenter Cohort Study

Abstract: Background: COVID-19 may be more frequent and more severe in cancer patients than in other individuals. Our aims were to assess the rate of COVID-19 in hospitalized cancer patients, to describe their demographic characteristics, clinical features and care trajectories, and to assess the mortality rate. Methods: This multicenter cohort study was based on the Electronic Health Records of the Assistance Publique-Hôpitaux de Paris (AP-HP). Cancer patients with a diagnosis of COVID-19 between 3 March and 19 May 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…However, in this category, patients referred in 2020 and presenting with a SARS-CoV-2 infection displayed a poorer survival than those without SARS-CoV-2 infection. This observation is perfectly in line with the 30-43% COVID-19-related mortality rate in patients with lung cancer, as reported in previous studies 10 , 11 .…”
Section: Discussionsupporting
confidence: 93%
“…However, in this category, patients referred in 2020 and presenting with a SARS-CoV-2 infection displayed a poorer survival than those without SARS-CoV-2 infection. This observation is perfectly in line with the 30-43% COVID-19-related mortality rate in patients with lung cancer, as reported in previous studies 10 , 11 .…”
Section: Discussionsupporting
confidence: 93%
“…However, we did not find that obesity had a negative effect on in-hospital mortality in cancer patients hospitalized for COVID-19. While this result may seem surprising since obesity is classically considered as contributing to a worse prognosis in the COVID-19 population [ 23 , 24 , 25 , 26 , 27 ], it is consistent with other studies [ 23 , 28 , 29 , 30 , 31 , 32 , 33 , 51 ] in cancer patients which did not find that mortality was increased (most ORs were close to 1 even after adjustment). This is the case, for example, for the cancer consortium cohort study, which found that obesity was not significantly associated with the risk of 30-day mortality, either in univariate analysis or after adjustment for age, sex, and smoking (OR = 0.99 [0.58–1.71]).…”
Section: Discussionsupporting
confidence: 87%
“…In numerous studies, obesity is associated with increased morbidity and mortality in patients with COVID-19 [ 23 , 24 , 25 , 26 , 27 ]. However, in some populations, there seems to be an obesity paradox, especially in severely ill populations such as respiratory failure or cancer patients [ 23 , 28 , 29 , 30 , 31 , 32 , 33 ]. Indeed, it appears that in these studies, obesity was not significantly associated with increased morbidity and mortality in cancer patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Second, low fT3 levels—often encountered in lung cancer patients with NTIS—have been indicated as independent predictor of the severity of COVID-19 disease [ 124 , 150 ]. Third, cancer [ 151 , 152 , 153 , 154 , 155 ], including lung cancer [ 153 , 154 , 155 ], has been recognized as risk factor for increased severity of COVID-19. Fourth, more research and long-term epidemiological surveillance are essential to answer whether the interplay between TH and COVID-19 can contribute to lung carcinogenesis or aggravate a preexisting lung malignancy [ 156 , 157 ].…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%